CONSTRAINTS ON THE AGE AND HALOGEN COMPOSITION OF MANTLE FLUIDS IN SIBERIAN COATED DIAMONDS - Burgess R.; Layzelle E.; Turner G.; Harris J.W. (My University, 2002)
Extension of the Ar–Ar stepped heating technique has been used to characterise the Ar, halogen (Cl, Br, I), Ca and K components in seven coated diamonds from the Aikhal kimberlite, Siberia. At least three components have been identified with different Ar isotope compositions. The major component is characterised by high 40Ar/36Ar >11 000 and constant 40Ar*/Cl (527±22×10−6), Br/Cl (1.74±0.18×10−3) and I/Cl (22.0±3.4×10−6) indicative of a mantle fluid phase. This component is widespread in coated diamonds having been previously reported in samples from Africa and Canada. Estimates of halogen abundances in the sub-continental mantle, based on data from African and Siberian coated diamonds, are 3 ppm Cl, 11 ppb Br and 0.4 ppb I. These low abundances, which are in good agreement with values derived for the depleted asthenospheric mantle derived from MORB data, imply that the upper mantle is >90% degassed of its halogens. A second Ar component in coated stones is most simply understood by in situ decay of 40K and is consistent with the coat-forming event occurring close to the time of host kimberlite eruption 350–380 Ma ago. A third Ar component has a low 40Ar/36Ar ratio (~300), is unassociated with release of K or halogens, and is most likely to be atmospheric blank.